What does the literature say about teaching methods for students with autism spectrum disorder? An integrative literature review - Orrico de Azevedo, Mariana Queiroz; Nunes, Débora R. P. (Education Policy Analysis Archives, 2018)
Considering the considerable number of students with autism who attend regular classes, it is necessary that teachers implement intervention practices that favor the academic development of this population. In this scenario, the primary purpose of this study is to identify, through an integrative literature review, teaching methods implemented by teachers of children with autism, in regular classes. In addition, this review aims to: identify student skills that were focus of the intervention studies; characterize the professional profile of the educators; describe the students’ characteristics and; based on the model of Libâneo (1994), characterize the teaching methods described. Theses and dissertations published in Brazil, between 2008 and 2013 were considered. The 20 studies identified revealed, for the most part, that teachers had limited professional training and students were behind in grade level. Only nine investigations focused on developing students' academic skills. The four teaching methods proposed by Libâneo (1994), associated or not with other practices, were identified. The results highlight the need of providing training programs that enable teachers to implement effective pedagogical practices in the education of students with autism.